Pelatihan Pembuatan Herbarium sebagai Media Penunjang Pembelajaran Materi Klasifikasi Biologi - Putri, Rossanita Truelovin Hadi; Meishanti, Ospa Pea Yuanita; Sholihah, Fatihatun Nikmatus; Huda, Moch. Faizul; Wulandari, Anggun (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2025)
The topic of classification of living organisms at the high school level still necessitates practical activities to foster students' kinesthetic skills, in addition to their critical and creative thinking abilities. Utilizing herbarium as a learning medium offers a solution to this challenge. The herbarium-making training aims to enable students to apply their theoretical knowledge through hands-on practical engagement. This approach is expected to provide students with diverse learning experiences throughout the educational process. Furthermore, students can also hone their creative thinking skills by participating in this herbarium-making training. This research employed a multi-stage methodology, including preparation, interviews, training, and evaluation. The findings of this study were derived from student response questionnaires regarding their learning experience with the herbarium-making training. The results showed that 100% of students found learning through herbarium creation to be highly enjoyable, and 87% of students indicated that this herbarium-making activity enhanced their hard skills and creative abilities